Generalisation of fear in PTSD related to prolonged childhood maltreatment: an experimental study - Thome, Janine; Hauschild, Sophie; Koppe, Georgia; Schmahl, Christian; Bohus, Martin (Psychological medicine, 2018)
BACKGROUND: Fear responses are particularly intense and persistent in post-traumatic stress disorder (PTSD), and can be evoked by unspecific cues that resemble the original traumatic event. Overgeneralisation of fear might be one of the underlying mechanisms. We investigated the generalisation and discrimination of fear in individuals with and without PTSD related to prolonged childhood maltreatment. METHODS: Sixty trauma-exposed women with (N = 30) and without (N = 30) PTSD and 30 healthy control participants (HC) underwent a fear conditioning and generalisation paradigm. In a contingency learning procedure, one of two circles of different sizes was associated with an electrical shock (danger cue), while the other circle represented a safety cue. During generalisation testing, online risk ratings, reaction times and fear-potentiated startle were measured in response to safety and danger cues as well as to eight generalisation stimuli, i.e. circles of parametrically varying size creating a continuum of similarity between the danger and safety cue. RESULTS: The increase in reaction times from the safety cue across the different generalisation classes to the danger cue was less pronounced in PTSD compared with HC. Moreover, PTSD participants expected higher risk of an aversive event independent of stimulus types and task. CONCLUSIONS: Alterations in generalisation constitute one part of fear memory alterations in PTSD. Neither the accuracy of a risk judgement nor the strength of the induced fear was affected. Instead, processing times as an index of uncertainty during risk judgements suggested a reduced differentiation between safety and threat in PTSD.
Gesehen am 05.11.2018
Article was first published online on 28 December 2017